Effects of unilateral and bilateral complex-contrast training on lower limb strength and jump performance in collegiate female volleyball players - Deng, B.; Yan, R.; Sui, X.; Lin, G.; Ding, S.; Li, D.; Sun, J. (PLOS ONE, 2025)
The concurrent development of strength and power is considered effective for improving jump performance in athletes.Although previous studies have examined the effects of unilateral and bilateral training, there is a lack of systematic research comparing the impact of these two training modes within the framework of Complex-Contrast Training (CCT) on female volleyball players. This study aimed to compare the effects of Unilateral Complex-Contrast Training (UCCT) and Bilateral Complex-Contrast Training (BCCT) on lower limb strength and jump performance in collegiate female volleyball athletes. A total of 16 female volleyball players were randomly assigned to either the UCCT group (n = 8) or the BCCT group (n = 8) using a random number-based randomization method. The training intervention consisted of 2 sessions per week for 8 weeks.Before and after the intervention, participants underwent a series of standardized tests, including Countermovement Jump (CMJ), Squat Jump (SJ), Drop Jump (DJ), Eccentric Utilization Rate (EUR), Standing Long Jump (SLJ), and one-repetition maximum (1-RM) squat. Statistical analysis was conducted using JASP version 0.18.3.0 with a 2 (group) × 2 (time) two-way repeated measures ANOVA. The results showed significant main effects of time (p < 0.001) for CMJ, DJ, SLJ, and 1-RM squat, while SJ and EUR did not exhibit significant improvements. A significant time × group interaction was found for CMJ (p = 0.009), and simple effects analysis indicated that the UCCT group showed a more pronounced improvement. No significant main effects of group or time × group interaction effects were observed for the other variables. Overall, UCCT demonstrated similar effects to BCCT in improving horizontal jump performance and maximal lower limb strength, but showed a greater advantage in enhancing vertical jump performance.